Metadata framework for online legal information system in Indian environment. Issue 1 (7th February 2017) - Bhardwaj, Raj Kumar; Margam, Madhusudhan
Abstract : Purpose: This study aims to discuss the metadata structure of an online legal information system (OLIS) developed to suit the Indian environment. The OLIS is accessible online atwww.olisindia.in . It contains several types of legal information resources to help lawyers, research scholars, students and the common user. The open-access OLIS helps the users to get the required information expeditiously. Dublin Core (DC) metadata standard was selected to create records in the OLIS because of ease of use and high adoption rate. Design/methodology/approach: The OLIS was designed using the system analysis and design method after a needs assessment survey conducted in eight major legal organizations in Delhi. The OLIS, accessible atwww.olisindia.in, was accessed to identify and validate the metadata elements with the DC metadata standard. Findings: This paper discusses in detail the metadata structures of the OLIS. The system contains 15 types of resources relating to judicial and legislative information. Each database has a different metadata framework so that information desired by the legal community can be retrieved with precision and quick recall. In addition, a number of functions, such as latest news, online help, Frequently Asked Questions, query submission, online discussion forum for help and video tutorials, have been integrated into the OLIS. Practical implications: The study guides law libraries and library professionals to follow metadata standards in building an open-access database and also provides a legal resources metadata framework that enables them to select suitable resources for their libraries. Originality/value: The study confirms that the metadata elements set for managing judicial and legislative information are different compared to other types of scholarly information. The study can help newly established law university libraries to build legal information systems to suit their environment and satisfy the information needs of the diverse law community.